2015
DOI: 10.1080/10942912.2015.1016577
|View full text |Cite
|
Sign up to set email alerts
|

Direct Acylation of Cyanidin-3-Glucoside with Lauric Acid in Blueberry and Its Stability Analysis

Abstract: dong Sun (2015): Direct acylation of cyanidin-3-glucoside with lauric acid in blueberry and its stability analysis, International Journal of Food Properties, ABSTRACTCyanidin-3-glucoside (C3G) is an anthocyanin that is abundant in blueberry. Lauric acid was used as the acyl donor in the acylation of C3G. Preparative high performance liquid chromatography was used to separate and purify the acylated C3G, the acylated rate was 30.78%. Fourier transform infrared spectroscopy and liquid chromatography mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Malvidin-3-glucoside with different saturated fatty acid chain lengths using an enzymatic synthesis were obtained with low yields (22-40%) [21]. Zhao et al described direct acylation of cyanidin-3-glucoside with lauric acid in blueberry, which was essentially chemical acylation with an acylated yield of 30.8% [18]. On the other hand, the optimal reaction conditions were more economical and efficient than the conditions mentioned in previous studies.…”
Section: Optimization Of Reaction and Model Validationmentioning
confidence: 96%
See 2 more Smart Citations
“…Malvidin-3-glucoside with different saturated fatty acid chain lengths using an enzymatic synthesis were obtained with low yields (22-40%) [21]. Zhao et al described direct acylation of cyanidin-3-glucoside with lauric acid in blueberry, which was essentially chemical acylation with an acylated yield of 30.8% [18]. On the other hand, the optimal reaction conditions were more economical and efficient than the conditions mentioned in previous studies.…”
Section: Optimization Of Reaction and Model Validationmentioning
confidence: 96%
“…Various methods, such as acylation [ 13 ], microencapsulation [ 14 ], and adding auxiliary compounds [ 15 , 16 ], have been attempted to increase the stability of anthocyanins in past decades. Therefore, chemical and enzymatic acylation have made substantial progress in improving the liposolubility and stability of anthocyanins in recent years [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Procyanidin B4 and malvidin-3-glucoside stearic acid derivatives were synthesized and characterized [ 17 ], and cyanidin-3-glucoside from blueberry was chemically acylated with lauric acid in vitro to produce Cy3glc-C12, in which the reaction (acylation rate: 30.78%) was continuously stirred for 48 h at 4 °C in DMF with Cy3glc (20 mg) and acyl donors, including lauric acid (1 equiv), 1-(3-dimethylaminopropy)-3-ethycarbodiimide (1.5 equiv) and N-hydroxybenzotriazole (1 equiv) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hybrid reaction was performed at 20°C and proceeded for 30 min. When the reaction was completed, methanol was used to stop the reaction (Zhao et al, 2015) Recovery of cell strains A frozen tube of H22 cell strain was taken out from liquid nitrogen tank, rapidly placed into 37°C water bath case, and shaken repetitively until no solid substance was left in the tube. The mouth of the frozen tube was cleaned with 75% ethanol on super clean bench.…”
Section: Chemical Acylation Proceduresmentioning
confidence: 99%
“…Yawadio and Morita proved that the color of black rice anthocyanin-rich fraction enhanced by adding carboxylic acids into the anthocyanin-glucosides medium [5] . Zhao et al acylated directly cyanidin-3-glucoside with lauric acid, and found that the stability of acylated cyanidin-3-glucoside was obviously higher than that of the unacylated cyanidin-3-glucoside [6] . At present, the acylation of anthocyanins is mainly from the separation of natural products, and the use of chemical methods to synthesize acylated anthocyanins is rarely reported.…”
Section: Introductionmentioning
confidence: 99%